Mechanical Properties, Structure and Machinability of the H13 Tool Steel Produced By Material Extrusion - Maly, Martin; Kolomy, Stepan; Kasan, Radek; Bartl, Lukas; Sedlak, Josef; Zouhar, Jan (Manufacturing Technology Journal, 2024)
The study focuses on an evaluation of mechanical properties of the H13 tool steel manufactured by the material extrusion and further comparison with conventionally produced material. Notably, for achieving sufficient surface quality of functional parts further post-processing is required. Thus, a comprehensive investigation, encompassing hardness, ultimate tensile strength (UTS) and yield strength (YS) measurement, microstructure, and machinability was performed. The material extrusion, an increasingly utilized additive manufacturing (AM) technique, offers a viable alternative to the prevalent laser powder bed fusion (LPBF) methods. This method enables a creation of complex geometries using various materials. The investigation revealed that the horizontal orientation of parts yielded the highest mechanical properties, reaching the ultimate tensile strength of approximately 1200 MPa. Additionally, the material exhibited the hardness of 47 HRC in the as-built state. The conventionally produced steel resulted in the higher UTS and YS in comparison to the AM material. The machinability of the as-built material in regard to cutting forces and surface roughness was also evaluated Lower surface roughness was achieved by decreasing feed per tooth. Optically measure material porosity was 6.13 % with maximum pore size 7.43 µm. The primary objective of this research is to optimize the mechanical properties of H13 tool steel post-printing, with a broader aim to apply the gained insights to improve other materials produced by the material extrusion.
Keywords: Material extrusion; H13 tool steel; Additive manufacturing; Microstructure; Mechanical properties